EPDM Elastomer and Biothermoplastic Polyester-based Silicate-layered Multifunctional Nanocomposites Incorporated with Poly(MA-alt-α-olefin)-g-APTS-SiO2 NPs and PP-g-MA by Reactive Extrusion Nanotechnology. Issue 17 (22nd November 2017) - Rzayev, Zakir M. O.; Göçmen, Bayram Ali; Demircan, Deniz; Kibarer, Günay
ABSTRACT: Multifunctional polymer blend nanocomposites consisting EPDM elastomer as a matrix polymer, bioengineering polyesters (PLA and PCL), PP- g -MA compatibilizer and covalently encapsulated colloidal alternating reactive copolymer- g -γ-aminopropyl trimethoxysilane-silica nanoparticles as reactive compatibilizer nanofillers, and organoclay (reactive ODA-MMT and complexable DMDA-MMT) nanofillers were fabricated in melt by a one-step reactive extrusion nanotechnology. The effects of bioengineering polyesters and their molecular mass, origin of organology, and reactive PP- g -MA compatibilizer were evaluated. Unique nanostructures, lower particle sizes and crystallinity, SEM–TEM morphologies, higher thermal behaviors, good mechanical and rheological properties of thermoplastic multifunctional nanocomposites were evaluated. GRAPHICAL ABSTRACT: